Trains for increased effectiveness and attractiveness / Tåg för ökad effektivitet och attraktivítet - Kottenhoff, Karl (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
Trains need to be effective and attractive to take a substantial market share. An important factor is the ticket price. The effectiveness must be increased. Operating costs can be reduced by e.g. modular train configuration, increased space utilization, double decekers and higher speeds. The last example, higher speeds, also increases the attractiveness of train riding. Other factors where stated preference interviews show that passengers’ willingeness to pay is high: low noise and vibration levels, good ventilation (AC), a varied seat configuration with adjustable seats, play-areas for children and service attributes as radio/music outlets at your seat and free coffe and tea in each coach. The impression of modernity itself also means a lot.